GLP-1 Agonists Reimagined: The Tripartite Applications of the Semaglutide Hormone - Park, Joon Daniel; Rahman, Merajur; Ye, Jeffrey (Technium BioChemMed, 2025)
Semaglutide, a GLP-1 receptor agonist has been initially adopted as a treatment and regulator for the Type 2 Diabetes disease. In this essay, we will be focusing on the three primary roles that the semaglutide fulfills throughout day to day life or in potential real world applications. We examined different hormones related to the endocrine system, and identified differences in weaknesses and strengths between GLP-1 and semaglutide. We also assessed the different roles that semaglutide may be used for. The original intended use being Type 2 Diabetes regulation, where we established the utilization of the potent insulin releasing trait of semaglutide being the key factor for Type 2 Diabetes regulation. A repurposed use for weight reduction, where we identified the secondary symptoms of insulin release such as lower appetite. Finally, a speculative application where the diabetes regulation capabilities may have a positive correlation in affecting neurological diseases such as dementia. Through the compilation and review of historic and recent sources, this paper highlights the broader usage of the semaglutide compound. The findings suggest that semaglutide’s mechanisms and variety makes it a promising candidate for future metabolic and potentially groundbreaking neurological medicine.